2005
DOI: 10.1007/s00125-005-0075-5
|View full text |Cite
|
Sign up to set email alerts
|

Acute in vivo effects of insulin on gene expression in adipose tissue in insulin-resistant and insulin-sensitive subjects

Abstract: Aims/hypothesis: We determined the response of selected genes to in vivo insulin in adipose tissue in 21 non-diabetic women. Materials and methods: The women were divided into insulin-sensitive and -resistant groups based on their median whole-body insulin sensitivity (8.7±0.4 vs 4.2±0.3 mg kg −1 min −1 for insulin-sensitive vs -resistant group). Subcutaneous adipose tissue biopsies were obtained before and after 3 and 6 h of i.v. maintained euglycaemic hyperinsulinaemia. Adipose tissue mRNA concentrations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
39
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 90 publications
(114 reference statements)
8
39
2
Order By: Relevance
“…Overexpression of Adipoq in obese mice decreases infiltration of macrophages into AT and release of proinflammatory cytokines from adipocytes and stromal vascular cells [36]. In humans, gene expression of ADIPOQ in AT and circulating concentrations of adiponectin are decreased in obese and insulin-resistant compared with nonobese and insulin-sensitive individuals [32,37]. In keeping with such data, in the present study, the obese group had significantly lower gene expression of ADIPOQ in AT than the non-obese group.…”
Section: Discussionsupporting
confidence: 85%
“…Overexpression of Adipoq in obese mice decreases infiltration of macrophages into AT and release of proinflammatory cytokines from adipocytes and stromal vascular cells [36]. In humans, gene expression of ADIPOQ in AT and circulating concentrations of adiponectin are decreased in obese and insulin-resistant compared with nonobese and insulin-sensitive individuals [32,37]. In keeping with such data, in the present study, the obese group had significantly lower gene expression of ADIPOQ in AT than the non-obese group.…”
Section: Discussionsupporting
confidence: 85%
“…Our study found that early insulin treatment significantly decreased IL-6 expression, which was inconsistent to a previous study, in which acute insulin infusion significantly stimulated the expression of IL-6, especially in insulin-resistant adipose tissue [10] . The discrepancies may be due to the different experimental procedures used (acute vs chronic).…”
Section: Wwwchinapharcom Chen X Et Alcontrasting
confidence: 99%
“…With insulin treatment, adiponectin expression was significantly increased in the obese mice. Our result is consistent with observation in other study [10] , in which mRNA concentration encoding adiponectin was increased significantly by acute euglycaemic hyperinsulinaemia in the insulin-sensitive adipose tissue. Insulin has also been reported to increase adiponectin secretion from omental but not subcutaneous adipocyte in human [18] .…”
Section: Wwwchinapharcom Chen X Et Alsupporting
confidence: 94%
See 1 more Smart Citation
“…This difference in magnitude may be due to the insulin sensitivity, obesity status of subjects, as well as the subjects' ethnic origins. First, a recent study showed that the expression of key genes in the inflammatory pathways was higher in the insulin-resistant than in the insulin-sensitive groups (Westerbacka et al 2006). Secondly, a chronic systemic low-grade inflammation is typically observed in obese subjects.…”
Section: Gadd45bmentioning
confidence: 99%